EXPERIENCE OF MEDICAL SERVICES TO THE PEOPLE OF DILI, TIMOR LESTE - Alkatiri, Fairuziah Binti Bader; Tan, Jacob Donald (2021)
This study aims to investigate the medical service provided in Dili, Timor Leste. The National Hospital become as the center of medical services for the people of Timor Leste, however there are still many complaints against the quality of medical services initiated by the dissatisfaction of the patient which is a state of higher concern. Applying the phenomenological approach, through purposive sampling, 7 patients with medical services experiences at the National Hospital were interviewed using open-ended questions and observed. The findings pointed towards the lack of several aspects such as available service rooms and their maintenance, clinical investigation options, quantity and quality of medical personnel, and the interaction between workers and patients. These four factors contribute negatively towards patient satisfaction, and yet enlighten national hospital management to enhance their medical service quality. It is hoped that the National Hospital will develop strategies to increase patient satisfaction and cater to the medical needs of Timorese.